DETERMINING BPKH FINANCIAL PERFORMANCE: A FINANCIAL RATIO AND VALUE FOR MONEY APPROACH - Ria Anisatus Sholihah; Jilma Dewi Ayu Ningtyas; Adinda Umul Fadzila (Nurul Jadid University, 2026)
This study examines the financial performance of the Indonesian Hajj Financial Management Agency (BPKH) from 2018 to 2023. The objective is to analyze BPKH's financial health and accountability through key performance indicators. The research employs a descriptive quantitative method, utilizing secondary data from BPKH’s official annual financial reports. Financial ratios analyzed include liquidity, solvency (Debt to Asset Ratio), investment (Investment to Fund Ratio and Return on Investment), and efficiency (Cost to Income Ratio). The results indicate that BPKH has successfully optimized hajj funds, evidenced by a significant increase in the Investment to Fund Ratio (RID) from 41.46% to 75.03%. While the Return on Investment (ROI) remains positive, the study identifies critical challenges, including a consistent decline in the Mandatory Liquidity ratio and a rising Cost-to-Income Ratio (CIR), which reached 3.32% in 2023. Furthermore, the Debt-to-Asset Ratio (DAR) remains above 100%, indicating that liabilities exceed assets. In conclusion, while overall performance is positive, BPKH must evaluate its asset-liability structure to ensure liquidity and implement stricter operational cost controls to maintain long-term sustainability and maintain the trust of pilgrims.